PENGARUH ULAMA IMAM LAPEO TERHADAP SPIRIT KEAGAMAAN DAN SOLIDARITAS SOSIAL KULTURAL MASYARAKAT MANDAR - muhammad, kamal (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2024)
The study of religious spirit or the spiritual aspect of human life has become a topic that has received increasing attention in recent decades, as the spiritual dimension is an integral part of human life. According to Weber, charismatic authority is a form of authority based on the extraordinary qualities possessed by a leader, In the discourse on religious spirit, it is often found that the charisma of religious figures affects social solidarity. This study uses a literature review method that can provide comprehensive theoretical insights into the topic or problem being studied, Religious practices and spirits of Mandar people have a significant influence on their social life, Ulama and religious figures such as lapeo priests have a strong influence on social decisions in Mandar society, Leadership and charisma of clerics are important in driving the socio-religious life of the community, overall, the religious practices of Mandar people have become a strong foundation in shaping social structures, values, and interaction patterns within the community. Ulama has a central role in the social life of Mandar society, the phenomenon of ulama charisma can be seen as one of the important indicators in understanding the dynamics of social solidarity in society, until today it is still easily observed in many cultural and traditions Mandar society.